Simonetta Polenghi, András Németh y Tomáš Kasper (eds.). Education and the body in Rurope (1900-1950). Movements, public health, pedagogical rules and cultural ideas - Morandi, Matteo (Historia y Memoria de la Educación, 2023)
Review